Identification of Central Regulators of Calcium Signaling and ECM–Receptor Interaction Genetically Associated With the Progression and Recurrence of Atrial Fibrillation - Büttner, Petra; Ueberham, Laura; Shoemaker, M. B.; Roden, Dan M.; Dinov, Borislav; Hindricks, Gerhard; Bollmann, Andreas; Husser, Daniela (Frontiers in Genetics, 2018)
Atrial fibrillation is a multifactorial disease with a strong genetic background. It is assumed that common and rare genetic variants contribute to the progression and recurrence of atrial fibrillation. The pathophysiological impact of those variants, especially when they are synonymous or non-coding, is often elusive and translation into functional experiments is difficult. In this study, we propose a method to go straight from genetic variants to defined gene targets. We focused on 55 genes from calcium signaling and 26 genes from extra cellular matrix ECM-receptor interaction that we found to be associated with the progression and recurrence of atrial fibrillation. These genes were mapped on protein-protein interaction data from three different databases. Based on the concept that central regulators are highly connected with their neighbors we identified central hub proteins according to random walk analysis derived scores representing interaction grade. Our approach resulted in the identification of EGFR, RYR2 and PRKCA (calcium signaling) and FN1 and LAMA1 (ECM-receptor interaction) which represent promising targets for further functional characterization or pharmaceutical intervention.